2013
DOI: 10.1152/ajprenal.00597.2012
|View full text |Cite
|
Sign up to set email alerts
|

SIRPα signaling regulates podocyte structure and function

Abstract: Signal-regulatory protein-α (SIRPα) is a transmembrane protein that contains tyrosine phosphorylation sites in its cytoplasmic region; two tyrosine phosphatases, SHP-1 and SHP-2, bind to these sites in a phosphorylation-dependent manner and transduce multiple intracellular signals. Recently, SIRPα was identified as one of the major tyrosine-phosphorylated proteins in the glomeruli and found to be expressed in podocytes. In the present study, we examined the role of SIRPα expression in podocytes using knockin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The level of the glomerular protein SIRPA was already decreased in the db/db vehicle mice compared to the healthy db/+ vehicle mice and insulin decreased the abundance even further. It has been shown to interact with nephrin in the slit diaphragm of the podocyte [ 38 ] and could be involved in podocyte injury [ 39 ]. Insulin also significantly decreased the abundance of GPR116 similar to SIRPA in the db/db mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The level of the glomerular protein SIRPA was already decreased in the db/db vehicle mice compared to the healthy db/+ vehicle mice and insulin decreased the abundance even further. It has been shown to interact with nephrin in the slit diaphragm of the podocyte [ 38 ] and could be involved in podocyte injury [ 39 ]. Insulin also significantly decreased the abundance of GPR116 similar to SIRPA in the db/db mice (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The binding of macrophage SIRPα to its widely expressed ligand, CD47, induces an inhibitory signal for phagocytosis, a “don’t eat me” signal 21 that prevents the phagocytosis of healthy cells. Mice with genetic inactivation or mutation of SIRPα have numerous abnormalities, including impairment of phagocyte migration 22 , dendritic cell (DCs) homeostasis 23 , bone cell differentiation 24 , kidney function 25 , and interleukin (IL)-17 and interferon (IFN)-γ production 26 . Phagocytes from SIRPα mutant mice also have enhanced respiratory bursts 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Albuminuria is one the most common symptoms in people with obesity-associated glomerular injury, which is characterized as glomeruli enlargement, focal segmental glomerulosclerosis, basement membrane thickening, and podocyte damage [3]. Recent studies focusing on podocyte physiology have indicated that podocyte structural and functional integrity is required for preventing glomerular albumin leakage and subsequent albuminuria [4, 5]. Previous study suggested that high glucose-induced oxidative stress initiated podocyte apoptosis and depletion both in vivo and in vitro [6], which represents an early mechanism driving diabetic nephropathy.…”
Section: Introductionmentioning
confidence: 99%